2017
DOI: 10.1073/pnas.1619666114
|View full text |Cite
|
Sign up to set email alerts
|

Color naming across languages reflects color use

Abstract: What determines how languages categorize colors? We analyzed results of the World Color Survey (WCS) of 110 languages to show that despite gross differences across languages, communication of chromatic chips is always better for warm colors (yellows/reds) than cool colors (blues/greens). We present an analysis of color statistics in a large databank of natural images curated by human observers for salient objects and show that objects tend to have warm rather than cool colors. These results suggest that the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
245
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(284 citation statements)
references
References 45 publications
27
245
2
1
Order By: Relevance
“…This analysis showed the greatest agreement for this five category partition. While the splitting of the blue category is reminiscent of findings from Russian speakers (Winawer et al., 2007), the more interesting finding is the unsplit warm category (i.e., red, orange, and yellow hues), which is consistent with the findings of Gibson et al. (2017) that the top free-choice colors of the Tsimanè do not include orange or pink.…”
supporting
confidence: 90%
“…This analysis showed the greatest agreement for this five category partition. While the splitting of the blue category is reminiscent of findings from Russian speakers (Winawer et al., 2007), the more interesting finding is the unsplit warm category (i.e., red, orange, and yellow hues), which is consistent with the findings of Gibson et al. (2017) that the top free-choice colors of the Tsimanè do not include orange or pink.…”
supporting
confidence: 90%
“…As stated in their title, Gibson et al. () argued that “color naming across languages reflects color use.” They presented this claim as an alternative to accounts of color naming based on perceptual salience. In support of this claim, they presented evidence of a warm–cool asymmetry in communicative need and a corresponding asymmetry in communicative precision in color naming across languages—suggesting that color naming systems may have adapted to a universal human tendency to communicate preferentially about warm colors.…”
Section: Discussionmentioning
confidence: 99%
“… Abstract Gibson et al. () argued that color naming is shaped by patterns of communicative need. In support of this claim, they showed that color naming systems across languages support more precise communication about warm colors than cool colors, and that the objects we talk about tend to be warm‐colored rather than cool‐colored.…”
mentioning
confidence: 99%
“…Other works such as Wnuk and Majid (2014) and Gibson et al (2017) demonstrate the role of culture in color and olfactory perception. And these hardly exhaust the studies.…”
Section: The Anthropology Of Numbers and Numerical Cognitionmentioning
confidence: 99%